Indonesian Culture Influence Towards English Directive Acts Used by Senior High School Students - Tamara Becce Tenridinanti; Indawan Syahri; Maribel Casinto Abalos; Rini Susanti (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTIn uttering the English language, especially English directive acts, Indonesian people do not deliver it directly, but they convey it long-winded. It is influenced by the Indonesian culture that tends to convolute in explaining something which is different from the English-speaking culture that speaks straight to the point. The objectives of the study were to identify the common types of directive illocutionary acts and to describe how the Indonesian culture is represented in English illocutionary acts made by the students of SMA Negeri 10 Palembang. The method of the study was descriptive-qualitative. The data was collected from twenty-six participants of SMA Negeri 10 Palembang through the role-play technique. Results of this study showed eight common types of English directive acts: commanding, requesting, suggesting, forbidding, questioning, permitting, encouraging, and wishing. Besides, the resemblance between the Indonesian culture and illocutionary acts has an interconnection shown in culture transfer. In this this study in particular, questioning was the most dominant directive act, and this is because Indonesian people tend to ask first before uttering straight to the point and suggesting was the second most dominant whereas requesting was the least dominant. ABSTRAKDalam pengucapan bahasa Inggris khususnya bahasa Inggris directive act, orang Indonesia tidak menyampaikannya secara langsung, tetapi menyampaikannya dengan bertele-tele. Hal tersebut dipengaruhi oleh budaya Indonesia yang berbelit-belit dalam menjelaskan sesuatu yang berbeda dengan budaya Inggris yang berbicara langsung ke intinya. Tujuan penelitian ini adalah untuk mengidentifikasi jenis-jenis ilokusi direktif yang umum dan mendeskripsikan bagaimana kemiripan budaya Indonesia dalam ilokusi bahasa Inggris yang dibuat oleh siswa SMA Negeri 10 Palembang. Metode penelitian adalah deskriptif kualitatif. Pengumpulan data dilakukan pada dua puluh enam peserta SMA Negeri 10 Palembang melalui peragaan role play. Studi ini menunjukkan delapan jenis tindakan direktif bahasa Inggris yang umum seperti memerintah, meminta, menyarankan, melarang, mempertanyakan, mengizinkan, mendorong, dan berharap. Selain itu, kemiripan budaya Indonesia dengan ilokusi memiliki keterkaitan yang terlihat dalam transfer budaya. Dari penelitian ini, bertanya sangat dominan karena masyarakat Indonesia cenderung bertanya terlebih dahulu sebelum berbicara langsung ke pokok permasalahan. Dominasi kedua menunjukkan, dan yang terakhir meminta.